A Proposed model for improving interactive electronic learning Methods - Al-Droubi, Lama Nazim (Journal of Educational and Psychological Sciences, 2020)
The aim of this research is to explore the most important features of interactive learning and its impact on the success of the educational process by discussing the educational methods used in the educational institutions and presenting the most important problems observed by students and teachers in the traditional educational process, In the educational institutions, and then try to explore the weakness of the educational process in which students find it difficult to education, by asking a questionnaire directed to different segments of the students were randomly selected from some of the university Which showed the need for students to introduce modern methods in education to increase the effectiveness of education and access to the ability to communicate more with teachers, so we have looked at the most important techniques that entered the educational process (electronic board, Which led to the transformation of the teaching process from its traditional form to interactive e-learning. Thus, relying on MVC technology, we introduced a reliable e-learning model to help interact between the learning process Taking into account the results of the questionnaire we have presented in advance. This model helps to standardize the various e-learning systems as a general framework that can be applied in different languages Software, and can handle various end-user operating platforms such as mobile phones with their various systems, computers, tablets and others.
Keywords: Interactive learning; Interactive learning tools; Educational model